2016
DOI: 10.1124/jpet.116.236067
|View full text |Cite
|
Sign up to set email alerts
|

Exploration ofα1-Antitrypsin Treatment Protocol for Islet Transplantation: Dosing Plan and Route of Administration

Abstract: Lifelong weekly infusions of human α1-antitrypsin (hAAT) are currently administered as augmentation therapy for patients with genetic AAT deficiency (AATD). Several recent clinical trials attempt to extend hAAT therapy to conditions outside AATD, including type 1 diabetes. Because the endpoint for AATD is primarily the reduction of risk for pulmonary emphysema, the present study explores hAAT dose protocols and routes of administration in attempt to optimize hAAT therapy for islet-related injury. Islet-grafted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In regard to CP increased distribution volume and half-life, since these distinctions appear to accompany this variant’s enhanced anti-inflammatory capacity, it is suggested that its physical properties render it functionally unique. It has been shown that exogenously administered hAAT is readily detected on the surface of activated immune cells ( 78 ), coinciding with observations by Subramaniyam et al, in which hAAT localizes on membrane lipid rafts ( 29 ). This property is in agreement with evidence for direct binding of oxidized cholesterol ( 31 ) and fatty acids ( 79 ) by hAAT, and suggests that hAAT membranal presence might serve as a platform for several of its functional attributes ( 80 82 ).…”
Section: Discussionsupporting
confidence: 79%
“…In regard to CP increased distribution volume and half-life, since these distinctions appear to accompany this variant’s enhanced anti-inflammatory capacity, it is suggested that its physical properties render it functionally unique. It has been shown that exogenously administered hAAT is readily detected on the surface of activated immune cells ( 78 ), coinciding with observations by Subramaniyam et al, in which hAAT localizes on membrane lipid rafts ( 29 ). This property is in agreement with evidence for direct binding of oxidized cholesterol ( 31 ) and fatty acids ( 79 ) by hAAT, and suggests that hAAT membranal presence might serve as a platform for several of its functional attributes ( 80 82 ).…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies show that human AAT dose protocols and routes of administration impact the protective effects of AAT therapy for islet-related injuries. 42 We found that infusion of 4 mg/mouse of AAT achieved better protection to human islet grafts compared to the lower dose of 2 mg/mouse. Our experience shows that the dose of human AAT needs to be optimized in different transplantation situations.…”
Section: Discussionmentioning
confidence: 72%
“…Previous reports with AAT in recent-onset type 1 diabetes included smaller study populations with a wide age variability, doses up to 90 mg/kg/dose, and no placebo group [17,18,19,20]. Higher doses of AAT (>120 mg/kg per dose) have been explored both in preclinical and clinical studies [23], with no evidence for dose-dependency beyond 120 mg/kg per dose. In 2018, we reported on periodic AAT treatment (up to 36 infusions) in a cohort as being safe and well tolerated during a surveillance period of 5 years [20].…”
Section: Discussionmentioning
confidence: 99%